The Role of Product Innovation, Accounting Competency, and Online Transactions (E-Commerce) in Increasing Competitiveness in MSMEs, Alalak District, Batola Regency, Indonesia - Anisah, Hastin Umi; Sustinah Limarjani; Rifqi Novriyandana; Rasidah (Open Access Indonesia Journal of Social Sciences, 2024)
Improving this economic aspect is by empowering the community economy, namely MSMEs owned by the community by maximizing the role of MSMEs. Maximizing the role of MSMEs must be supported by business management aspects such as the application of product innovation, accounting competencies, and online transactions (e-commerce) to increase MSMEs' competitiveness. By increasing the competitiveness of MSMEs, it is hoped that it can improve community welfare. This research aims to explore the role of product innovation, accounting competency and online transactions (e-commerce) in increasing competitiveness in MSMEs. Alalak District, Batola Regency, Indonesia. Quantitative research methods were used in this research with the PLS analysis technique. Observation of indicators is carried out using instruments (questionnaires) which aim to find out respondents' opinions about something. The results of this research reveal that product innovation, accounting competence, and online transactions (e-Commerce) can increase the competitiveness of MSMEs.